Cerebral phaeohyphomycosis in liver transplant recipient: A case report. Issue 12 (5th December 2022) - Ullah, Kaleem; Baig, Muhammad Asif; Dogar, Abdul Wahab; Uddin, Shams; Fatir, Chaudhary Abdul; Asad, Ali; Tahir, Muhammad Junaid; Lee, Ka Yiu; Mohamed Ahmed, Khabab Abbasher Hussien; Yousaf, Zohaib
Abstract: Cerebral phaeohyphomycosis is a fungal brain infection with a high fatality rate. It is caused by dematiaceous fungi and is increasingly recognized as a cause of serious illness in both immunocompetent and immunocompromised patients. We report cerebral phaeohyphomycosis in a liver transplant recipient. He was treated with multiple surgeries and antifungals and made a complete recovery. This report highlights that early and aggressive surgical intervention and extended antifungal coverage can have a positive outcome even in immunocompromised patients. The fungal infection in immunocompromised patients should be considered and treated aggressively. Abstract : Cerebral phaeohyphomycosis is a fungal brain infection with a high fatality rate. Early and aggressive surgical intervention and extended antifungal coverage can have a positive outcome even in immunocompromised patients. The fungal infection in immunocompromised patients should be considered and treated aggressively.